2016
DOI: 10.1364/oe.24.013946
|View full text |Cite
|
Sign up to set email alerts
|

High gain holmium-doped fibre amplifiers

Abstract: Abstract:We investigate the operation of holmium-doped fibre amplifiers (HDFAs) in the 2.1 µm spectral region. For the first time we demonstrate a diode-pumped HDFA. This amplifier provides a peak gain of 25 dB at 2040 nm with a 15 dB gain window spanning the wavelength range 2030 -2100 nm with an external noise figure (NF) of 4-6 dB. We also compare the operation of HDFAs when pumped at 1950 nm and 2008 nm. The 1950 nm pumped HDFA provides 41 dB peak gain at 2060 nm with 15 dB of gain spanning the wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…Kamynin et al(2015)in their paper have demonstrated the maximum gain of 35.8dB for 2050nm of wavelength. Although the spectral range for the reported experiment was 2020nm to 2120nm [8].For the first time diode pumped HDFA was demonstratedby researcher Simakov et al(2016)He reported the peak gain of 25dB at 2040nm [5]. Resonantly pumped holmium-doped fiber amplifier was reported by Hemming et al(2014) which is highest power amplifier, it is capable of operating in an atmospheric transmission window >2.05µm [6].…”
Section: Doped Fibermentioning
confidence: 99%
“…Kamynin et al(2015)in their paper have demonstrated the maximum gain of 35.8dB for 2050nm of wavelength. Although the spectral range for the reported experiment was 2020nm to 2120nm [8].For the first time diode pumped HDFA was demonstratedby researcher Simakov et al(2016)He reported the peak gain of 25dB at 2040nm [5]. Resonantly pumped holmium-doped fiber amplifier was reported by Hemming et al(2014) which is highest power amplifier, it is capable of operating in an atmospheric transmission window >2.05µm [6].…”
Section: Doped Fibermentioning
confidence: 99%
“…Первый гольмиевый волоконный усилитель был создан на длине волны 2100 нм [9]. Накачка усилителя производилась иттербиевым во-локонным лазером на длине волны 1125 нм, а выходная мощность со-ставила 1,65 Вт при входном сигнале 35 мВт.…”
Section: Amplification Of Picoseconds Pulses Of Two Microns Spectral unclassified
“…Among them, the development of high-power lasers for LIDAR (due to its excellent atmospheric transmission), gas sensing, medicine, material processing, and nonlinear optical conversion in the mid-infrared. [1][2][3][4][5] In this context, many efforts have been made to improve the performance of holmium-doped fiber lasers. One interesting strategy is using a tapered-doped fiber to increase the absorption of the pump along the doped core, which consequently helps improve the power conversion between the pump and signal.…”
Section: Introductionmentioning
confidence: 99%